Test purchase, synthesis, and characterization of 2‐methoxydiphenidine (MXP) and differentiation from its meta‐ and para‐substituted isomers. Issue 1 (15th April 2015) - McLaughlin, Gavin; Morris, Noreen; Kavanagh, Pierce V.; Power, John D.; O'Brien, John; Talbot, Brian; Elliott, Simon P.; Wallach, Jason; Hoang, Khoa; Morris, Hamilton; Brandt, Simon D.
Abstract : The structurally diverse nature of the 1, 2‐diphenylethylamine template provides access to a range of substances for drug discovery work but some have attracted attention as 'research chemicals'. The most recent examples include diphenidine, i.e. 1‐(1, 2‐diphenylethyl)piperidine and 2‐methoxydiphenidine, i.e. 1‐[1‐(2‐methoxyphenyl)‐2‐phenylethyl]piperidine (MXP, methoxyphenidine, 2‐MXP) that have been associated with uncompetitive N ‐methyl‐D‐aspartate (NMDA) receptor antagonist activity. Analytical challenges encountered during chemical analysis include the presence of positional isomers. Three powdered samples suspected to contain 2‐MXP were obtained from three Internet retailers in the United Kingdom and subjected to analytical characterization by gas chromatography (GC) and high performance liquid chromatography (HPLC) coupled to various forms of mass spectrometry (MS). Nuclear magnetic resonance spectroscopy, infrared spectroscopy and thin layer chromatography were also employed. This was supported by the synthesis of all three isomers (2‐, 3‐ and 4‐MXP) by two different synthetic routes. The analytical data obtained for the three purchased samples were consistent with the synthesized 2‐MXP standard and the differentiation between the isomers was possible. Distinct stability differences were observed for all three isomers during in‐source collision‐induced dissociation of the protonated molecule when employing detection under HPLC selected‐ion monitoring detection, which added to the ability to differentiate between them. Furthermore, the analysis of a 2‐MXP tablet by matrix assisted inlet ionization Orbitrap mass spectrometry confirmed that it was possible to detect the protonated molecule of 2‐MXP directly from the tablet surface following addition of 3‐nitrobenzonitrile as the matrix. Copyright © 2015 John Wiley & Sons, Ltd. Abstract : 2‐Methoxydiphenidine (2‐MXP) has recently appeared as a 'research chemical' and is suspected to show dissociative properties in humans. This study presents the identification of 2‐MXP in various products obtained from test purchases from UK‐based vendors. Further verification was obtained by organic synthesis of three positional MXP isomers. Furthermore, the implementation of matrix assisted inlet ionization Orbitrap mass spectrometry confirmed the ability to detect the protonated molecule of 2‐MXP directly from the tablet surface following addition of 3‐nitrobenzonitrile as the matrix.